Leadership development from contemplative positive psychology in public adminitration, a review of the literature - Rueda-Sánchez, Susana Iris; Mombiela-Guillén, María del Carmen (Acciones e Investigaciones Sociales, 2023)
This literature review considers the processe of change faced by societies and organisations and, coherently, by the civil service. There are many elements that will promote change in public administrations, but all of them will be inadequate without the human factor. For this reason, the review is based on the conclusions of the studies that have reinforced the relevant contributions of leadership to organisational change processes, to the results, to the health and well-being of the workforce, with leadership being an important line of study within positive psychology. Similary, there are numerous lines of research focused on understanding the psychological and neurobiological effects produced by contemplative practices such as mindfulness. Therefore, its of interest to review and relate these constructs and design interventions that confirm a positive relationship between contemplative practices and leadership development in the civil service.
Keywords: leadership; contemplative science; mindfulness; public service